Kepemimpinan Manajerial dalam Meningkatkan Mutu Pendidikan Tinggi; TelaÃ¢â¬â¢ah Kritis Augustus E. Osseo Asare - Ustmani, Mujib (EDUKASI: Jurnal Pendidikan Islam, 2013)
This critical study examines the relationship between efficiency and effectiveness of the quality management practices adopted by the UK, how quality management practices and the relationship between management efficiency "and" effectiveness of leadership "in the UK. Well as the relationship between the degree of effectiveness and efficiency of quality management practices will provide the framework conceptual work that will enable academics and practitioners to critically reflect on the efficiency and effectiveness of teaching and research quality improvement decisions and actions to ensure the successful implementation of TQM best practices and evaluate managerial leadership in higher education.